2017
DOI: 10.1177/1010428317691674
|View full text |Cite
|
Sign up to set email alerts
|

MiR-613 suppresses retinoblastoma cell proliferation, invasion, and tumor formation by targeting E2F5

Abstract: Retinoblastoma is a common intraocular malignancy that occurs during childhood. MicroRNAs play critical roles in the regulation of retinoblastoma initiation and progression, and aberrant expression of miR-613 had been reported in various types of cancer. However, the role and mechanism of its function in retinoblastoma are still unclear. In this study, we found that miR-613 was downregulated in retinoblastoma tissues and cell lines. Overexpression of miR-613 suppressed retinoblastoma cell proliferation, migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
(35 reference statements)
4
28
0
Order By: Relevance
“…LncRNA DANCR is over‐expressed in osteosarcoma cell proliferation, migration, invasion, and xenograft tumor growth in vitro and in vivo and regulates osteosarcoma stemness features by upregulating AXL via miR‐33a‐5p inhibition (Jiang et al, ). Besides, Zhang, Zhu et al () have reported that miR‐613 suppresses retinoblastoma cell proliferation, invasion, and tumor formation by targeting E2F5, which is closely correlated with our study.…”
Section: Discussionsupporting
confidence: 90%
“…LncRNA DANCR is over‐expressed in osteosarcoma cell proliferation, migration, invasion, and xenograft tumor growth in vitro and in vivo and regulates osteosarcoma stemness features by upregulating AXL via miR‐33a‐5p inhibition (Jiang et al, ). Besides, Zhang, Zhu et al () have reported that miR‐613 suppresses retinoblastoma cell proliferation, invasion, and tumor formation by targeting E2F5, which is closely correlated with our study.…”
Section: Discussionsupporting
confidence: 90%
“…Besides that, E2F5 had been verified as a direct target of several miRNAs and had negative association with their expression, such as miR-129-3p [36], miR-132 [37] and miR-613 [38]. In present research, miR-1271-5p was found to directly target E2F5 and was inversely regulated its expression in OC.…”
Section: Discussionsupporting
confidence: 55%
“…12 Recently, abnormally expressed miRNAs were broadly implicated in retinoblastoma development. [13][14][15] However, the biological role of miR-214-3p in retinoblastoma is still largely unclear. In this study, miRNA array analysis revealed that miR-214-3p was significantly down-regulated in retinoblastoma tissues.…”
Section: Introductionmentioning
confidence: 99%